The undercounting of child-mother births - Juan Pablo Chauvin; Rafael Rubi\~ao; Miguel Ángel Talamas Marcos (Inter-American Development Bank (IDB), 2025)
Accurate demographic data are essential for effective policy design, yet private costs may deter individuals from truthfully reporting sensitive information. We examine this market failure and its implications in the context of child motherhood. Using administrative records from Brazil, Mexico, and the United States, along with census data from 59 countries, we identify systematic patterns of under-reporting, indicating that child motherhood is significantly more prevalent than previously thought. Births to mothers aged 10-14 are often missing from contemporary administrative records but appear in censuses conducted a decade later, with under-counting in birth registries reaching 20-30% in Brazil, Mexico, and the United States. We introduce a model where reporting decisions weigh instrumental benefits against age-dependent private costs, yielding predictions that align with observed patterns: truthful reporting increases markedly with the mothers age, under-reporting of child-mother births decreases with the time elapsed between data collection and childbirth, and retrospective census estimates generally provide more accurate birth counts than contemporary administrative records for this age group, but not for older mothers. Our findings suggest that social costs, rather than fear of legal repercussions, are a primary driver of under-reporting.
Keywords: J13; D10; J18; D82; 330; child motherhood; private information; social norms